2021
DOI: 10.1111/spol.12706
|View full text |Cite
|
Sign up to set email alerts
|

How does she do it all? Effects of education on reconciliation of employment and informal caregiving among Austrian women

Abstract: The introduction of reforms to the Austrian pension system in the early 2000s resulted in a significant increase in the employment rate of older working age women. This increase was highly differentiated along education groups, with increases in employment rates concentrated among those with secondary and tertiary education. Logistic regression analysis is applied to SHARE data from waves 1 and 6, to determine whether the increase in labour market participation of women aged 50+ in Austria has affected informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
2
5
1
Order By: Relevance
“…A recent European study showed that women with lower education were more likely to provide high intensity care than men [ 68 ] and even if our study did not approach the differences between educational background within WKCs, our results show that more women than men engaged in long weekly care hours and reported a decreased ability to work or study due to informal care provision, which might affect their educational opportunities in the long run.…”
Section: Discussioncontrasting
confidence: 69%
“…A recent European study showed that women with lower education were more likely to provide high intensity care than men [ 68 ] and even if our study did not approach the differences between educational background within WKCs, our results show that more women than men engaged in long weekly care hours and reported a decreased ability to work or study due to informal care provision, which might affect their educational opportunities in the long run.…”
Section: Discussioncontrasting
confidence: 69%
“…Caregiving may therefore be associated with previously existing inequalities (e.g. in income and health) and there is indeed some evidence that family caregiving, particularly of intense form, may be becoming increasingly concentrated on disfavoured groups (Rodrigues & Ilinca, 2021). Our findings reinforce the view that women may be particularly vulnerable to such accumulation of disadvantages.…”
Section: Discussionsupporting
confidence: 78%
“…This reversal of the gender care gap for care provided outside the household used to happen much earlier and has been delayed for later-born cohorts due to the cohort effects we show for men. The decreasing likelihood of caregiving outside the household for later-born cohorts of men could be linked to increases in statutory retirement age that have led to the postponement of the age at which men shift their time to unpaid caregiving ( Rodrigues & Ilinca, 2021 ). The occurrence of caregiving to someone outside the household has apparently remained the same among women, even when faced with similar increases in the statutory retirement age.…”
Section: Discussionmentioning
confidence: 99%
“…However, as countries moved to raise retirement age, an increasing share of women in their “encore years” are postponing retirement and remaining in full-time employment. This may reduce their availability to provide care outside their household ( Rodrigues & Ilinca, 2021 ). In addition, current cohorts of women approaching retirement age have experienced a combination of delayed childbearing and increased longevity of their older relatives often spent in poor health, resulting in greater shared life years with older parents, as well as adult children ( Moen, 2016 ; Patterson & Margolis, 2019 ).…”
mentioning
confidence: 99%